LASER THERAPY IN THE COMPLEX TREATMENT OF PATIENTS WITH LYMPHEDEMA OF THE LOWER EXTREMITIES - Yarovenko, G.V. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Optimization of the results of complex treatment of patients with lymphatic edema of the extremities. Materials and methods: Comprehensive treatment with the use of laser therapy was conducted in 46 patients aged from 19 to 73 years. By the method of serial sampling, all patients were grouped into 2 groups of I-III stages of lymphedema. The first group of patients with primary lymphedema of the lower extremities – 6, the second group with secondary lymphedema – 40 people. In the treatment of patients, conservative therapy was used in combination with physiotherapeutic methods such as intravenous laser irradiation of blood. The assessment of microcirculation of the lower extremities was carried out using computer thermography. The resorption function of the lymphatic system of the affected limb was studied using the hydrophilic test McClura and Aldrich. Results: Clinical improvement of the manifestations of the disease, positive changes in the lymphatic drainage, microcirculation, condition of the soft tissues of the lower extremities, mainly in patients with stages I and II, confirmed by thermography, ultrasound examination of the inguinal lymph nodes and soft tissues, hydrophilic sample of McClura and Aldrich. Conclusion: The use of intravenous laser irradiation of blood has been shown to increase the effectiveness of complex treatment of patients with lymphedema of the lower extremities.